The Aquatic Productivity using The Indicator of Plankton Diversity and Abundance in Telaga Dringo, Indonesia - Rahayu, Nur Laila; Hilmi, Endang; Artini, Dewi; Listyaningrum, Sisca Febrianti; Widyatama, Rodrigo Tyas Perwira; Ansah, Anang Adri (Universitas Atma Jaya Yogyakarta, 2024)
Aquatic productivity is the most basic trophic level in every aquatic ecosystem. Lake Dringo is a protected area and one of the highest lakes on the island of Java. Ecosystem balance can be seen from the study of water productivity. The purpose of this study was to determine the primary productivity and secondary productivity of waters in the Lake Dringo Nature Reserve, Central Java. The purposive sampling method was used in this study by establishing five stations and three replications at each station. The combination of primary and secondary productivity has a total abundance of 22,491-38,556 ind/liter. The highest abundance was Chlorophyta at 33% while the lowest abundance was Rotifera at 4%. This shows that there is no species dominance so that the primary productivity of the waters is still good.